PROSPECTS FOR THE DEVELOPMENT OF TRUNK DIAGNOSTICS - Mansurov Mukhtorjon Toxirjonovich; M. Yusupjonova (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article provides a brief analysis of the formation and current status of the main gas pipeline diagnostics. The development of local defect detectors and the scope of their application in industry are shown, examples of the creation of external defect detection scanners for use in capital repairs are given. Data on standard and problematic sections of gas pipelines are provided in terms of the use of in-line fault detection. Depending on the diameter of the gas pipeline and the working pressure, the range of typical fault detection tools is indicated. The problems encountered in the use of modern in-line facilities in gas pipelines, including technical, economic and organizational aspects, are listed.